2013
DOI: 10.2174/1566524013666131111130058
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical Applications of Zinc Oxide Nanomaterials

Abstract: Nanotechnology has witnessed tremendous advancement over the last several decades. Zinc oxide (ZnO), which can exhibit a wide variety of nanostructures, possesses unique semiconducting, optical, and piezoelectric properties hence has been investigated for a wide variety of applications. One of the most important features of ZnO nanomaterials is low toxicity and biodegradability. Zn2+ is an indispensable trace element for adults (~10 mg of Zn2+ per day is recommended) and it is involved in various aspects of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
302
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 563 publications
(344 citation statements)
references
References 115 publications
2
302
0
4
Order By: Relevance
“…ZnO is an environmental-friendly material which has been used in medical applications such as cancer treatments and DNA detection 27,28) , and nowadays is widely being studied for dental applications 29,30) . In endodontic treatment, it is well known that particle size plays a key role on root canal disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…ZnO is an environmental-friendly material which has been used in medical applications such as cancer treatments and DNA detection 27,28) , and nowadays is widely being studied for dental applications 29,30) . In endodontic treatment, it is well known that particle size plays a key role on root canal disinfection.…”
Section: Discussionmentioning
confidence: 99%
“…40 =29,000 g/mol)), and deionized water as solvents were used as the starting raw materials. In this work, chemicals were purchased from Sigma-Aldrich Co., (St Louis, MO, USA); they were of standard research grade and were used without further purification.…”
Section: Experimental Section Materialsmentioning
confidence: 99%
“…35,36 Antibacterial activity, catalysis, gas sensors, and diodes are further examples of suitable applications. [37][38][39][40] Different ZnO nanomaterial forms (such as nanorods, 41,42 nanotubes and nanowires, 43,44 nanocrystals, 45,46 nanoclusters, 47 nanofibers, 48,49 and numerous forms nanostructures) have been produced by using various methods whereas these materials revealed that different characteristics allowed for several applications to be practically produced. 50,51 As can be seen from literature, several techniques such as precipitation, 52 microwave hydrothermal, 53 sonochemical, 54,55 solvothermal, 56 chemical, 57,58 thermal treatment, 59 and sol-gel 60,61 can be used to create ZnO nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured ZnO possess high surface area, good chemical stability and nontoxic 27 . The bio synthesized ZnO nanoparticles are trusted to be friendly with the environment, bio safe and biocompatible 28 . It also has bio medical application as drug carriers 29 , used in cosmetics and as fillers in medical materials 30,31 .…”
Section: Introductionmentioning
confidence: 99%